Fingerprints – are they unique human’s codes? - Mumelaš, S. (Open Schools Journal for Open Science, 2020)
Have you ever looked carefully at your fingertips? What do you see? You can see many bumps and bridges on your fingertips. Those patterns are called dermatoglyphs. Dactyloscopy is a discipline that uses papillary lines. Fingerprints can be used in solving crimes, like key or password to open the phone or tablets. They are formed before the birth and they are permanent and unique. There are three main patterns in fingerprints: arch, loop and whorl. Are there any similarities between human fingerprints? We decided to test are the human fingerprints inherited. We took fingerprint patterns among members of the same family and as well among group of students in the class. After the investigation we confirm that there are some similarities in fingerprints among the members among the same family.